IMPACT OF STRESS MANAGEMENT AMONG ACADEMICIANS WITH SPECIAL REFERENCE TO BANGALORE - Jaggaiah, Dr. Tripuraneni; Balaji, Dr. T.; S, Suganya (The journal of contemporary issues in business and government, 2021)
Stress is an inseparable part of life. Each and every individual realize and face stress at every walk of life. It affects all the sections of society such as poor, rich, children, and aged people, literate and illiterate. Stress is difficult to define precisely. Stress affects not only our physical health but our mental wellbeing too. To successfully manage stress in everyday life, an individual can learn to relax and enjoy life. The best way to manage stress is to prevent it. This may not be always possible. So, the next best thing is to reduce stress and make life easier. This present study is based on primary as well as secondary data in nature. The primary data have been collected from different college lectures/faculties of India. For the purpose of study, the Impact of stress is identified and categorized into two dimensions. Each dimension contains a series of statements pertaining to impact of stress. For that purpose, the institution has to take measures such as creating stress free work environment and creating awareness about stress and its consequences on individual family and on institution and must provide stress management programs to cope with stress. Stress free work environment prevents stress related problems and improves the job satisfaction, loyalty which in turn provides better quality of work.